The middle way is antidote to extremism - Bakar, Osman (New Straits Times Press (M) Bhd., 2023)
The middle way or path understood in the moral sense is the true answer to extremism. Its very definition implies the truth of this statement. Let the middle way prevail and extremism would have no sanctuary.